Animal personal and trait theory - Kairys, Antanas; Liniauskaitė, Audronė (Psichologija, 2014)
Humans are perhaps the only animal species capable of abstract thinking, creating theories, and understanding themselves. This capability comes with a sort of arrogance – a belief that traits common to humans are completely unique and not like those found in other animals. In this paper, we analyze animal personality research: the concept of animal personality, research methods, and the potential value of animal personality research in developing trait theory. The ability to declare that there, indeed, is such a phenomenon as animal personality depends on what we define as personality. If we say that the core aspects of personality are the subconscious or Self, then we are unable to discuss animal personality. However, if we assume that personality can be described as stable behavior patterns, then, when discussing stable behavior patterns of animals, the use of the term “personality” seems justified. There is an abundance of terms and descriptions not only in human but also in animal personality research: the terms like animal temperament, behavior types or syndromes are all used just to avoid the term “personality”. All methods of animal personality research can be classified into two large categories: rating-based and behavior-coding based methods. Both categories of methods are widely used (especially behavior coding), yet there still is a lot of debate regarding their superiority, since both methods have pros and cons. Rating-based methods produce more stable results, have better inter-rater reliability; however, they are much more susceptible to anthropomorphism. Behavior-coding-based methods, albeit more objective, also have their problems: they are less stable, can encompass only a limited scope of observed behavior, and, amongst other things, they also have ecological validity and sample formation issues. It is reasonable to say that both methods should be used, and studies that apply both of these methods to the same sample are especially valuable.Despite methodological problems, animal personality research can be beneficial in several aspects. Animal personality research can provide us with a better understanding of animal behavior patterns and the evolution of human personality, it can also expand research possibilities (e.g., it is possible to perform breeding studies). However, most research requires some sort of a theoretical background to provide guidelines for researchers regarding key points and methods of the study. Personality trait theory (namely the Big Five) seems to be a feasible theoretical basis for animal personality studies; however the research in the field is still in its infancy. The reviewed studies allow us to conclude that animal personality research, be it a relatively unpopular and somewhat controversial field, is still not only very important for the development of personality theories, but also has a practical value. After a significant improvement in research methods and trait theory, we can expect a better understanding of the evolution of human personality; these improvements would also mean a more precise animal selection process, improvements in animal well-being, and similar theoretical and practical benefits.
Keywords: personality; animal personality; personality traits